Self-propagating synthesis of Zn-loaded biochar for tetracycline elimination - Wang, Wei; Gao, Ming; Cao, Mengbo; Dan, Jianming; Yang, Hongbing (The Science of the total environment, 2021)
Herein, a novel Zn-loaded biochar (Zn-LBC) originating from Fraxinus pennsylvanica Marsh leaves was successfully prepared through a simple and rapid self-propagating combustion reaction (SHS) and could serve as an efficient adsorbent for tetracycline (TC) elimination from water. The adsorption performance was analyzed via a series of characterizations and batch adsorption experiments. The results showed that the novel adsorbent Zn-LBC exhibited an excellent TC adsorption capacity (159.64 mg/g), which was 2.63 times higher than that of the original biochar (60.78 mg/g). The pseudo-second-order kinetic model and Freundlich isothermal model fit the adsorption data well. It is noteworthy that Zn-LBC had little effect on the adsorption capacity of TC in the 0–10 mg/L various coexisting ion range and presence of humic acid (HA). In addition, the adsorption test of TC using hospital wastewater as the water sample also achieved satisfactory results (raw influent: 52.65 mg/g, final effluent: 85.64 mg/g). FT-IR and XPS investigations showed that the TC adsorption mechanism included surface complexation, π-π interactions, and hydrogen bonds. The results provide new ideas for exploring low-cost and highly efficient modified biochar adsorbent for TC elimination. [Display omitted] •Zn-loaded biochar was successfully prepared by self-propagating combustion method.•The self-propagating combustion is facile, effective and time-saving (30 min).•Excellent adsorption performance (159.64 mg/g) of tetracycline was achieved.•Adsorption mechanism included surface complexation, π-π interactions and H-bond.